Oxalate poisoning of lactating cows in pasture of setaria - Schenk, Maria Aparecida Moreira; Faria Filho, Tancredo Theodoro de; Pimentel, Dorival Monteiro; Thiago, Luiz Roberto Lopes de S. (Pesquisa Agropecuaria Brasileira, 2014)
A herd of 85 Nelore cows with two-months old calves and in poor conditions transferred to a pasture of Setaria anceps cv. Kazungula in the State of Mato Grosso do Sul, Brazil. After ten days, 45 of these cows showed clinical signs of oxalate poisoning characterized by staggaring, tetany, diarrhea, and nasal discharge, sometimes bloody, and nine of them died. The present study was conducted to confirm the suspected oxalate poisoning. The studies revealed that the plasma calcium concentration in animals suspected of poisoning was lower than normal. Levels of oxalates in new plant growth were very high (average 6.2%). Soils in the area contained 140 ppm of potassium, which could account for the high levels of oxalate in the grass. The most evident histopathological finding was the presence of a great number of oxalate crystals in the renal tubules, in the one cow on which post-mortem examination was done. Blood hypocalcemia and plant levels of oxalate associated with histopathological findings strongly suggest oxalate poisoning as the cause of the outbreak studied. Management practices to prevent oxalate poisoning are suggested.